RECANALIZATION OUTCOMES IN ACUTE ISCHEMIC STROKE PATIENTS AT THONG NHAT HOSPITAL AND ASSOCIATED FACTORS - Minh Quang, Trần; Thị Phương Nga, Nguyễn (Journal of Health and Aging, 2025)
Early vascular recanalization in acute ischemic stroke is an effective therapeutic strategy for neurological recovery; however, the outcome is influenced by various patient-related and baseline factors. To evaluate the effectiveness of recanalization therapy and investigate factors associated with neurological improvement in patients with acute ischemic stroke. A retrospective descriptive study was conducted on 186 acute ischemic stroke patients treated at Thong Nhat Hospital from January 2024 to March 2025. Clinical assessments (NIHSS, mRS), degree of recanalization (TICI), and associated factors were analyzed. The proportion of patients with NIHSS improvement ≥4 points was high in the thrombectomy-only and bridging therapy groups, at 80,7% and 90,3%, respectively. The highest rate of complete recanalization (TICI 3) was observed in the bridging therapy group (64,5%). The highest proportion of favorable functional outcome at discharge (mRS 0–2) was seen in the IV thrombolysis-only group (80,6%). Factors significantly associated with neurological improvement included: baseline mRS 0–2 (p=0,016), pre-intervention blood pressure (p
Keywords: acute ischemic stroke; thrombolysis; endovascular intervention; NIHSS; mRS; TICI